The Effect of Young Leaves Extract of Arumanis Mango as an Antidepressant in Zebrafish (Danio rerio) - Risda Arba Ulfa; Tri Cahyanto; Ikeu Winda Larasati; Adisty Virakawugi Darniwa; Ayuni Adawiyah; Afriansyah Fadillah (Jurnal Biologi Tropis, 2022)
Sustained stress is risked for the emergence of various diseases including disability to depression. Clinically, antidepressant drugs are still the main option even though they are known have side effects for users. Therefore, various types of drug plants that have the potential as natural antidepressants have begun to be used, one of them is the young leaf of mango (Mangifera indica). It is known contains various bioactive compounds, including mangiferin which is useful as an antioxidant, anti-inflammatory, and plays a role in protecting nervous tissue. This study aimed to determine the effect of MangoÃ¢â¬â¢s young leaves extract of Arumanis cultivar as an antidepressant in zebrafish (Danio rerio) exposed to Unpredictable Chronic Stress (UCS). The method used is Completely Randomized Design (CRD) which consists of 3 treatments, namely K (Aquadest); P1 (extract concentration 10ÃÂµg/mL); and P2 (extract concentration 20ÃÂµg/mL). The parameters include the antioxidant activity and behavioral tests, namely new tank diving and light/dark preferences. The results showed that exposure to UCS tends to increased anxiety as indicated by a decrease in exploration on behavioral test. The data showed that the MangoÃ¢â¬â¢s young leaves extract induction with a concentration of 20ÃÂµg/mL obtained the highest value percentage in the exploration of the upper area (36.8 s) and the preference of the bright area (90.8 s) significantly. The induction of mangoÃ¢â¬â¢s young leaves extract has the potential as an antidepressant in zebrafish exposed to UCS with an optimal concentration of 20ÃÂµg/ml.